Eradication of Human Trafficking Crimes in Myanmar: Pemberantasan Tindak Pidana Perdagangan Orang di Myanmar - Angelika Giovani; Marcell William Sondang Hutagaol (Universitas Muhammadiyah Sidoarjo, 2026)
General Background Human trafficking constitutes a serious form of transnational organized crime that directly violates human rights and disproportionately targets vulnerable populations, particularly migrant workers. Specific Background In Southeast Asia, Myanmar—especially the Myawaddy region following the 2021 coup—has emerged as a hub for online scamming operations and forced labor exploitation involving Indonesian nationals. Knowledge Gap Despite extensive victim repatriation efforts, limitations remain in cross-border law enforcement due to the absence of bilateral extradition arrangements and ongoing political instability in Myanmar. Aims This study examines Indonesia’s juridical responses to trafficking cases involving Indonesian citizens in Myanmar by analyzing the fulfillment of legal elements under Law No. 21 of 2007 and the application of international criminal law principles. Results The findings demonstrate that the cases meet all constituent elements of trafficking, namely actus reus, means, and mens rea, enabling Indonesia to invoke active and passive nationality principles, supported by Mutual Legal Assistance, INTERPOL Red Notice mechanisms, and ASEAN cooperation frameworks. Novelty The study highlights the strategic reliance on regional and international legal instruments as substitutes for formal extradition in a conflict-affected jurisdiction. Implications Strengthening ASEAN commitments, advancing an ASEAN Extradition Treaty, and optimizing existing cooperative mechanisms are essential to reinforce cross-border accountability and protection of Indonesian victims of human trafficking. Highlights: Trafficking cases involving Indonesian citizens satisfied all statutory elements under national anti-trafficking law. Active and passive nationality principles provide a legal basis for prosecution and victim protection beyond territorial limits. Regional and international cooperation mechanisms function as critical alternatives amid absent bilateral extradition arrangements. Keywords: Human Trafficking, Myanmar, Bilateral Cooperation